The CXCL16-CXCR6 axis in glioblastoma modulates T-cell activity in a spatiotemporal context - Chia, Tzu-Yi; Billingham, Leah K.; Boland, Lauren; Katz, Joshua L.; Arrieta, Victor A.; Shireman, Jack; Rosas, Aurora-Lopez; DeLay, Susan L.; Zillinger, Kaylee; Geng, Yuheng; Kruger, Jeandre; Silvers, Caylee; et al. (Frontiers in Immunology, 2024)
A crucial facet of GBM pathobiology is its profound ability to induce immunosuppression within the tumor microenvironment, which is primarily orchestrated by immunosuppressive tumor-associated myeloid cells (TAMCs). Myeloid cells are pivotal in shaping the GBM microenvironment and modulating immune responses, and direct physical interactions with effector immune cells play a critical role in these processes. While these interactions can foster antitumor immunity by presenting tumor antigens to T cells, they can also promote immunosuppression by inhibiting effector immune cell functions. Our study highlights the critical role of the CXCR6/CXCL16 axis in T-cell myeloid interactions within GBM tissues. Specifically, our data revealed that CXCL16 surface expression is limited to TAMCs, whereas microglia release CXCL16 as a cytokine. Consequently, T cells predominantly engage with TAMCs, leading to impaired T-cell function within the tumor environment. Conversely, our findings also underscore the essential role of CXCR6 expression in Tcell activation and initial migration to tumor tissues. Thus, the CXCL16-CXCR6 axis has dualistic characteristics: it facilitates the early stages of the T-cell immune response, facilitating T-cell infiltration into tumors, but once inside the tumor, it promotes immunosuppression. These results suggest that while targeting the CXCL16/CXCR6 axis has therapeutic potential in GBM, carefully considering the timing and context of intervention is crucial.